Women and Kula - Susanne Kuehling (Suomen Antropologi)
This article argues that the hosting of kula partners is an important part of the exchange system that requires more attention. Women’s management of their households and resources, their training of children, and the internal networks that provide for a visiting kula partner are regarded as the benefits and key motivations (‘profit’) of kula. If the hospitality is underwhelming, a visitor will not continue the partnership and, because he will share his experiences back home, this will negatively affect the future kula affairs of that household. By isolating the movements of valuables from the deep experiences of visiting and hosting, the role of women in kula is typically misrepresented as marginal and of lower value. Kula, to me and to most islanders, is not about the fame of traders, but about the cooperation of families to ensure the services, hospitality, and generosity that are so special to the region.